1996
DOI: 10.1002/(sici)1096-8628(19960329)62:3<224::aid-ajmg4>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Thomas syndrome: Potter sequence with cleft lip/palate and cardiac anomalies

Abstract: Holzgreve et al. [Am J Med Genet 18:177–184, 1984] first reported on a syndrome including renal anomalies, heart defect, polydactyly, and cleft palate with other oropharyngeal anomalies. We report here on four sibs with renal adysplasia associated in two with cardiovascular malformations and cleft lip or cleft palate in two. We propose that these patients as the two siblings reported by Thomas et al. [Am J Med Genet 45:767–769, 1993] are affected with a syndrome different of the one described by Holzgreve et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The cleft lip and palate, which is admittedly settled in a syndromic entity, may rather be the result of oligohydramnios than of genetic abnormalities and may fit well in the Potter sequence. Thomas et al (1993) reported a new syndrome that associated Potter sequence, cleft lip and palate, and cardiac abnormalities (Zlotogora et al, 1996; Briscioli et al, 1997). Our case presented a Thomas syndrome associated with a Potter sequence and a bilateral cleft lip and palate, agenesis of the right branch of the pulmonary artery, and agenesis of the right pulmonary veins and inter‐atrial communication.…”
Section: Discussionmentioning
confidence: 99%
“…The cleft lip and palate, which is admittedly settled in a syndromic entity, may rather be the result of oligohydramnios than of genetic abnormalities and may fit well in the Potter sequence. Thomas et al (1993) reported a new syndrome that associated Potter sequence, cleft lip and palate, and cardiac abnormalities (Zlotogora et al, 1996; Briscioli et al, 1997). Our case presented a Thomas syndrome associated with a Potter sequence and a bilateral cleft lip and palate, agenesis of the right branch of the pulmonary artery, and agenesis of the right pulmonary veins and inter‐atrial communication.…”
Section: Discussionmentioning
confidence: 99%
“…During embryogenesis, cells from the pharyngeal arches contribute to both mandibular and cardiovascular development [12,13]. While not lethal in utero, craniofacial defects are known to be linked to (often lethal) congenital cardiovascular defects in some human genetic disorders [14][15][16]. Interestingly, an Fgf8 mutant phenotype also displays defects in pharyngeal arch-derived structures, with remarkable resemblance to human 22q11 deletion syndrome [17,18].…”
Section: Discussionmentioning
confidence: 99%